Models and operators for extension of active multimedia documents via annotations - Martins, Diogo Santana (2013)
Multimedia production is an elaborate activity composed of multiple information management and transformation tasks that support an underlying creative goal. Examples of these activities are structuring, organization, modification and versioning of media elements, all of which depend on the maintenance of supporting documentation and metadata. In professional productions, which can count on proper human and material resources, such documentation is maintained by the production crew, being key to secure a high quality in the final content. In less resourceful configurations, such as amateur-oriented productions, at least reasonable quality standards are desirable in most cases, however the perceived difficulty in managing and transforming content can inhibit amateurs on producing content with acceptable quality. This problem has been tackled in many fronts, for instance via annotation methods, smart browsing methods and authoring techniques, just to name a few. In this dissertation, the primary objective is to take advantage of user-created annotations in order to aid amateur-oriented multimedia authoring. In order to support this objective, the contributions are built around an authoring approach based on structured multimedia documents. First, a custom language for Web-based multimedia documents is defined, based on SMIL (Synchronized Multimedia Integration Language). This language brings several contributions, such as the formalization of an extended graph-based temporal layout model, live editing of document elements and extended reuse features. Second, a model for document annotation and an algebra for document transformations are defined, both of which allows composition and extraction of multimedia document fragments based on annotations. Third, the previous contributions are integrated into a Web-based authoring tool, which allows manipulating a document while it is active. Such manipulations encompass several interaction techniques for enriching, editing, publishing and extending multimedia documents. The contributions have been instantiated with multimedia sessions obtained from synchronous collaboration tools, in scenarios of video-based lectures, meetings and video-based qualitative research. Such instantiations demonstrate the applicability and utility of the contributions